Is adjunctive CBT really effective for schizophrenia?: COMMENTARY ON… COCHRANE CORNER. (September 2019) - Reid, Katherine
SUMMARY: Although antipsychotic medication remains the mainstay of treatment for schizophrenia, medications alone are not always successful. Cognitive–behavioural therapy (CBT) is recommended as an adjunct to pharmacological treatment. The Cochrane review under consideration evaluates the effects of offering CBT as an add-on to standard care compared with standard care alone, and this commentary puts those findings into their clinical context. DECLARATION OF INTEREST: None.